The prognostic significance of erythrocyte sedimentation rate in COVID-19 - Kaya,Tezcan (2021)
SUMMARY OBJECTIVE: There are limited data about the significance of erythrocyte sedimentation rate as a single prognostic parameter for the prognosis and mortality of COVID-19. This study aimed to investigate the diagnostic utility of erythrocyte sedimentation rate as a prognostic factor for the disease severity and mortality in patients with COVID-19. METHODS: A total of 148 consecutive patients with a confirmed diagnosis of COVID-19 and hospitalized at the intensive care unit or non-the intensive care unit were included in the study. The patients were allocated to groups as severe/critical disease versus nonsevere disease and survivors and nonsurvivors. The prognostic role and predictable values of erythrocyte sedimentation rate were analyzed. RESULTS: Erythrocyte sedimentation rate was found to be higher among patients with severe/critical disease compared to those with nonsevere disease (p<0.001) and among nonsurvivors compared to survivors (p<0.001). The logistic regression analysis showed that erythrocyte sedimentation rate was an independent parameter for predicting disease severity and mortality. The role of erythrocyte sedimentation rate in the assessment of severity and mortality in patients with COVID-19 was analyzed using the receiver operating characteristic curve and was found to be significant in both. The analyses suggested that the optimum erythrocyte sedimentation rate cutoff point for disease severity and mortality were 52.5 mm/h with 65.5% sensitivity and 76.3% specificity and 56.5 mm/h with 66.7% sensitivity and 72.5% specificity. CONCLUSION: Our results suggest that erythrocyte sedimentation rate was an independent prognostic factor for severity and mortality in patients with COVID-19.